Influence of Honeybee Attractants in Enhancing the Seed Productivity and Quality of Onion Seed Crop - JYOTHI M NAIK; JB GOPALI; BAPURAYAGOUDA PATIL; VINAY KUMAR MM (Seed Research, 2026)
Onion (Allium cepa) is a commercial crop among bulb crops. It is highly cross-pollinated and depends on various pollinating agents. Therefore the studies were carried out to assess the influence of honey bee attractants in enhancing the productivity and quality of onion seed at Haveli farm, University of Horticultural Sciences, Bagalkot, Karnataka, India during rabi season 2017-18. The experiment involves treatments such as, T1- fennel seed oil (0.5%), T2- dill seed oil (0.5%), T3- cumin seed oil (0.5%), T4- fenugreek seed oil (0.5%), T5- jaggery solution (10%), T6- sugar solution (10%) and T7- control. The onion crop was sprayed with these attractants at 10-15% per cent flowering and during 50 per cent flowering. Among the various treatments imposed, spraying of jaggery solution at 10 per cent (T5) increased the bee visitations in both first and second spray and was on par with sugar solution at 10% (T6). The quantitative and qualitative parameters like number of seeds per umbel (19.17),thousand seed weight (3.98g), seed yield (8.97q/ha), seed germination (96.67%), seedling length (8.86cm), vigour index (857) and seedling dry weight (0.022mg) were significantly higher in seed crop sprayed with jaggery solution at 10 per cent (T5) compared to other treatments. The results of present investigation conclusively revealed that spraying of jaggery solution at 10 per cent is most economical, feasible and adoptable by the farming community.